2017
DOI: 10.2147/ahmt.s110859
|View full text |Cite
|
Sign up to set email alerts
|

Gender nonconforming youth: current perspectives

Abstract: Beginning with a case vignette, a discussion follows of the reformulation of theories of gender development taking into consideration the recent upsurge of gender nonconforming and transgender youth presenting for gender services and also in the culture at large. The three predominant models of pediatric gender care are reviewed and critiqued, along with a presentation of the recently developed interdisciplinary model of gender care optimal in the treatment of gender nonconforming youth seeking either puberty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(22 citation statements)
references
References 22 publications
1
15
0
6
Order By: Relevance
“…Going further, some reviews concluded that being affirmed socially in their identified gender provided “substantial improvements in their mental health” (Riley 2018, 204) compared to transgender children not affirmed (even though there was no such comparison group in the studies) or that mental health disparities would be resolved “immediately” (Cicero and Wesp 2017, 6) if children were affirmed in their gender identity or that, if children were so affirmed, disparities in “emotional distress are reduced or eliminated” (Gower et al 2018, 788). One review concluded that given parental support, transgender children would “thrive” (Ehrensaft 2017, 64), while another review concluded that anxiety and depression were both found to have decreased in Olson’s (2016b) study (Allen, Watson, and VanMattson 2019, 3). Another review (Kuvalanka, Gardner, and Munroe 2019, 103) mentioned that there were no differences in depression in Olson et al’s (2016b) study, but said nothing about anxiety or self-worth, leaving the impression that there were probably no other variables of interest besides depression.…”
Section: Discussionmentioning
confidence: 99%
“…Going further, some reviews concluded that being affirmed socially in their identified gender provided “substantial improvements in their mental health” (Riley 2018, 204) compared to transgender children not affirmed (even though there was no such comparison group in the studies) or that mental health disparities would be resolved “immediately” (Cicero and Wesp 2017, 6) if children were affirmed in their gender identity or that, if children were so affirmed, disparities in “emotional distress are reduced or eliminated” (Gower et al 2018, 788). One review concluded that given parental support, transgender children would “thrive” (Ehrensaft 2017, 64), while another review concluded that anxiety and depression were both found to have decreased in Olson’s (2016b) study (Allen, Watson, and VanMattson 2019, 3). Another review (Kuvalanka, Gardner, and Munroe 2019, 103) mentioned that there were no differences in depression in Olson et al’s (2016b) study, but said nothing about anxiety or self-worth, leaving the impression that there were probably no other variables of interest besides depression.…”
Section: Discussionmentioning
confidence: 99%
“…This was contrary to LGBT ideology and the activity of Dr. Zucker was since long time under pressure from LGBT activists. In spite of the acknowledged existence of various treatment models of gender identity disorder [77], the administration of Centre for Addiction and Mental Health decided to launch an external review of the activity of Dr. Zucker [75]. Two reviewers wrote in their report "in the course of this review, two predominant themes emerged as areas of concern for the reviewers: firstly, the GIC appears to operate as an insular entity within CAMH and the community at large, and secondly, the GIC appears to be out of step with current clinical and operational practices.…”
Section: Harassment Of Dissentersmentioning
confidence: 99%
“…Dabei kann es lebenslang, besonders in Zusammenhang mit Eintritt in die Pubertät, Partnersuche, Heirat, Schwangerschaft und Elternschaft, zu Ergänzungen und Neubewertungen kommen (40). Die Geschlechtsidentität ist also nicht statisch, sondern variabel über alle Entwicklungsstadien des Menschen hinweg (15).…”
Section: Geschlechtsdysphorie Bei Jugendlichen Und Erwachsenen (30285)unclassified